THE INFLUENCE OF EXERCISE HABITS, EXERCISE MOTIVATION AND BODY MASS INDEX ON PHYSICAL FITNESS IN STUDENTS OF JUNIOR HIGH SCHOOL - Yusrifar Mujibuddin; Nurdin, Fatah; Puspitorini, Wahyuningtyas; Subandi, Oman Unju; Nasution, Harry Syahputra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study was to determine the effect of exercise motivation, exercise habits and body mass index on the physical fitness of junior high school students. This study uses associative quantitative research methods, with test and non-test techniques. The analysis technique uses a path analysis approach. The population in this study was a junior high school with a total of 80 students, with the selection of samples using simple random sampling method, namely by taking samples at random. Based on the results of this study it can be interpreted that (1) There is an insignificant effect of exercise habits on body mass index of 23.4% (2) There is a significant effect of exercise motivation on body mass index of 27.3% (3) There is an insignificant effect a significant effect of exercise habits on physical fitness is 0.1% (4) There is a non-significant effect of motivation to exercise on physical fitness of 44.7% (5) an insignificant effect of body mass index on physical fitness is 2.8% (6 ) There is a non-significant effect of motivation to exercise through body mass index on physical fitness of 0.8 and (7) There is an insignificant effect of exercise habits through body mass index on physical fitness of 0.6